52.8k views
4 votes
Solve the equation. Round to the nearest hundredth. Show work.


4e^(5x) - e^(-x) = -3e^(2x)

User Keisar
by
5.5k points

1 Answer

2 votes

Answer:

The value of x = -0.46

Explanation:


4e^(5x)-e^(-x)=-3e^(2x) ÷
e^(-x)


(4e^(5x))/(e^(-x))-(e^(-x))/(e^(-x))=(-3e^(2x))/(e^(-x))

* Subtract the power of the same bases


4e^(6x)-1=-3e^(3x)

* Let
e^(3x)=y


e^(6x)=y^(2)

∴ 4y² - 1 = -3y

∴ 4y² + 3y - 1 = 0 ⇒ factorize

∴ (4y - 1)(y + 1) = 0

∴ y + 1 = 0 ⇒ y = -1

∴ 4y - 1 = 0 ⇒ 4y = 1 ⇒ y = 1/4


y=e^(3x)

∴ y = -1 refused (
e^(ax) never gives -ve value)


e^(3x)=1/4 ⇒ insert ln in both sides


lne^(ax)=axln(e)=axln(e) = 1

∴ 3xln(e) = ln(1/4)

∴ 3x = ln(1/4)

∴ x = [ln(1/4)] ÷ 3 = -0.46

User Mbded
by
5.3k points